Nursing categories' perceptions of the practice environment and quality of care in North West Province: a cross-sectional survey design - Lufuno M. E. Mphaphuli; Siedine K. Coetzee; Babalwa Tau; Suria M. Ellis (BMC, 2024)
Abstract Background There is a substantial amount of literature on the perception of the practice environment and quality of care as perceived by registered nurses and community services nurses in South Africa and worldwide, but there is little to no research that could be found regarding other categories of nurses, and how these perceptions differ between the different categories. Therefore, the aim of this study is to describe the different nursing categories' perceptions of the practice environment and quality of care and the association between the variables. Methods This study applied a cross-sectional survey design. Data were collected in April 2021 in the public sector of the North West Province. Multiphase sampling was applied to all categories of nurses who worked in an in-patient unit in the selected hospital for at least 3 months (n = 236). Results All nursing categories perceived the practice environment as negative, regarding nurse participation in hospital affairs; nurse manager ability, leadership, and support of nurses and staffing and resource adequacy. Perceived quality of care and patient safety items were perceived as neutral and good. However, in all instances, the perceptions of community service nurses and registered nurses were most negative, and enrolled nurse assistants most positive. Adverse events towards patients and nurses were perceived to only occur a few times a year. Overall, nurse perceptions of quality of care and patient safety were most correlated with the subscale of nurse foundations of quality of care and nurse manager ability, leadership, and support of nurses. Adverse events towards patients were most correlated with the collegial nurse-physician relationship subscale, while adverse events towards nurses were correlated with the foundations of quality of care subscale. Conclusion Improving the practice environment, especially regarding the subscale nurse foundations of quality of care and nurse manager ability, leadership, and support of nurses, is associated with improved quality of care. Nurses with higher qualifications, registered nurses and community service nurses rated quality of care lower than other categories of nurses, contributing to literature that higher qualified staff are more competent to assess the practice environment and quality of care.